Gender and youth responsiveness considerations for targeting, testing and scaling suitable CSA practices and technologies: Learnings from the Climate-Smart Villages - Beal, Catherine; Castellanos, Andrea Estefania; Martínez, Jesús David; Ouedraogo, Mathieu; Recha, John W.M.; Radeny, Maren A.O.; Läderach, Peter R.D.; Bonilla-Findji, Osana (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This working paper summarizes the findings of a portfolio review conducted to explore the gender and youth responsiveness of climate-smart agriculture technologies tested across climate-smart villages. The innovative and integrative aspect of the Climate-Smart Village (CSV) approach can provide useful insights into how to decrease the gender gap in the context of climate change. The diverse settings of CSVs (across East and West Africa, South and Southeast Asia and Latin America) and long program timeline, present a unique opportunity to gather learnings for the broader agriculture research for development community and practitioners. Toward these points, this paper aims to assess how gender and youth responsiveness was integrated into the process of identifying, testing, promoting, and scaling suitable CSA practices and technologies in the context of the implementation of the CSV approach. The review found that collective action and local partner engagement has proved to be very successful in the CSVs in regards to gender outcomes. To improve the gender and youth responsiveness of CSVs, it is essential taking those considerations into account from the very beginning of the project design, as well as having a GSI expert involved.